Marketers' five shades of green: Getting personal with strategic positioning. Issue 10 (14th September 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Five strategies are described that are built upon value drivers for green products such as image, status, functionality and brand management through authenticity and superior offerings. Also emphasized is the importance of strategies that target commercial markets for green products, which represent valuable opportunities for growth. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.